MEDICAL NEGLIGENCE AND THE RES IPSA LOQUITUR DOCTRINE IN THE ADMINISTRATION OF CANCER TREATMENT IN SOUTH AFRICA - CA Maimela (Obiter, 2022)
Medical negligence is one of the leading socio-economic challenges faced by the health sector in South Africa and across the globe. This is attributed to the fact that millions of Rands are paid out by private and public hospitals to victims of medical malpractice on a daily basis, with dire consequences. For example, health establishments, particularly in the public sector, are unable to realise their duty to provide health care to millions of disadvantaged people as enshrined by section 27(1) of the Constitution as funds meant to provide health care go instead towards the payment of medical malpractice claims. Furthermore, medical practitioners in private and public hospitals now practise defensive medicine in order to avoid being sued for medical malpractice and this results in compromised health care for patients. This contribution aims to prove that people living with cancer can be exposed to medical malpractice just like patients who suffer from any other chronic medical condition, and also to dispel the myths connected to cancer treatment and care from a medical and a social perspective. In addition to the above, the contribution exposes the importance of the res ipsa loquitur doctrine (the thing speaks for itself) in solving complex medical negligence cases, with the aim of ensuring that justice is served to all patients living with cancer or other health impairments.